Cross roads [large type] : a novel - Young, William P. (FaithWords, 2012)
"Anthony Spencer is egotistical, proud of being a self-made business success at the peak of his game, even though the cost of winning was painfully high. A cerebral hemorrhage leaves Tony comatose in a hospital ICU. He 'awakens' to find himself in a surreal world, a 'living' landscape that mirrors dimensions of his earthly life, from the beautiful to the corrupt. It is here that he has vivid interactions with others he assumes are projections of his own subconscious, but whose directions he follows nonetheless with the possibility that they might lead to authenticity and perhaps, redemption. The adventure draws Tony into deep relational entanglements where he is able to 'see' through the literal eyes and experiences of others, but is "blind" to the consequences of hiding his personal agenda and loss that emerge to war against the processes of healing and trust. Will this unexpected coalescing of events cause Tony to examine his life and realize he built a house of cards on the poisoned grounds of a broken heart? Will he also have the courage to make a critical choice that can undo a major injustice he set in motion before falling into a coma?"--